2007
DOI: 10.1051/parasite/2007143231
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability ofTriatoma rubrovaria(Reduviidae: Triatominae) from Brazil, Argentina and Uruguay as revealed by two different molecular markers

Abstract: Summary :Randomly amplified polymorphic DNA (RAPD) and nuclear ribosomal DNA sequence analyses were used to assess the genetic population structure of the South American triatomine species Triatoma rubrovaria throughout its geographical distribution. To investigate the genetic variability at both intraspecific and intrapopulational levels the RAPD profiles and the nucleotide sequences of the rDNA intergenic spacers, ITS-1 and ITS-2, were analysed and compared. The phenetic analysis based on RAPD profiles show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
(20 reference statements)
1
7
0
1
Order By: Relevance
“…24 Recently, the potential adaptation of this bug to new environments was suggested by its genomic plasticity shown by the high intraspecific genetic variability detected in populations of T. rubrovaria from Brazil, Uruguay, and Argentina through molecular markers. 58 In our previous study, precipitin assays performed on the collected bugs showed one specimen of T. rubrovaria positive to human antiserum in Branquillos, a settlement closer to the urban perimeter of Quaraí. 29 This study on the genetic and biological characterization of T. cruzi isolates obtained from T. rubrovaria showed its pathogenicity and virulence in experimental animals.…”
Section: Discussionmentioning
confidence: 85%
“…24 Recently, the potential adaptation of this bug to new environments was suggested by its genomic plasticity shown by the high intraspecific genetic variability detected in populations of T. rubrovaria from Brazil, Uruguay, and Argentina through molecular markers. 58 In our previous study, precipitin assays performed on the collected bugs showed one specimen of T. rubrovaria positive to human antiserum in Branquillos, a settlement closer to the urban perimeter of Quaraí. 29 This study on the genetic and biological characterization of T. cruzi isolates obtained from T. rubrovaria showed its pathogenicity and virulence in experimental animals.…”
Section: Discussionmentioning
confidence: 85%
“…The very scarce ITS-2 sequence differences between T. arthurneivai and T. rubrovaria , a species known in southern Brazil, Uruguay and northern Argentina [75], pose doubts on whether to keep the validity of T. arthurneivai as independent species. Recent genetic and morphometric studies have already raised several questions about T. arthurneivai , indicating that topotypes from Minas Geraes may represent a species different from populations of São Paulo State formerly also referred to T. arthurneivai and suggesting that these São Paulo populations might probably belong to T. wygodzinskyi [76].…”
Section: Discussionmentioning
confidence: 99%
“…Os espaçadores ribossomais internos ITS-1 e ITS-2, localizados entre as regiões 18S e 28S, também são bons marcadores para esses tipos de estudo, tendo sido utilizado para filogenia de espécies do gênero Panstrongylus (Marcilla et al 2002), taxonomia alfa e filogenia dos complexos T. phyllosoma (Martínez et al 2006) e T. dimidiata s.l. presentes no México (Tamay-Segovia et al 2008, Herrera-Aguilar et al 2009) e genética de populações de T. rubrovaria na Argentina, Brasil e Uruguai (Pacheco et al 2007).…”
Section: Sequenciamento De Dnaunclassified